2019
DOI: 10.3390/fi11060124
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Vehicles Geolocalization Using LoRaWAN

Abstract: One of the main drawbacks of Global Navigation Satellite Sytems (GNSS) is that they do not work indoors. When inside, there is often no direct line from the satellite signals to the device and the ultra high frequency (UHF) used is blocked by thick, solid materials such as brick, metal, stone or wood. In this paper, we describe a solution based on the Long Range Wide Area Network (LoRaWAN) technology to geolocalise vehicles indoors. Through estimation of the behaviour of a LoRaWAN channel and using trilaterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 24 publications
0
10
0
3
Order By: Relevance
“…The capability to penetrate objects causing NLOS combined with the long-range reading makes LoRa a viable sensing technology for robust localization in large indoor spaces with various NLOS situations using a small number of static anchors. More specifically, a study on vehicle tracking in a large indoor parking garage (180 m × 80 m) shows promising localization results with only three anchors [68]. Since buildings commonly have various objects blocking the signals, using other sensing technologies that do not penetrate objects well would require several anchors installed to make sure a certain number of anchors are seen from all the localizations in the building.…”
Section: Long Range (Lora)mentioning
confidence: 99%
“…The capability to penetrate objects causing NLOS combined with the long-range reading makes LoRa a viable sensing technology for robust localization in large indoor spaces with various NLOS situations using a small number of static anchors. More specifically, a study on vehicle tracking in a large indoor parking garage (180 m × 80 m) shows promising localization results with only three anchors [68]. Since buildings commonly have various objects blocking the signals, using other sensing technologies that do not penetrate objects well would require several anchors installed to make sure a certain number of anchors are seen from all the localizations in the building.…”
Section: Long Range (Lora)mentioning
confidence: 99%
“…Percebe-se que no ponto de intersecc ¸ão entre elas tem-se o emissor. A distância entre o transmissor e o receptor pode ser calculada através da Equac ¸ão 1, que é derivada de um modelo empírico [Manzoni et al 2019]. Onde d é a distância entre receptor e emissor, RSSI é o indicador de potência do sinal, e n é um valor experimental, normalmente entre 2 e 6, que representa o fator de perda de sinal.…”
Section: Indicador De Potência Do Sinal Recebido -Rssiunclassified
“…Já Manzoni et. al, [Manzoni et al 2019] realiza a geolocalizac ¸ão de veículos em um ambiente interno usando uma rede LoRa. Com uma arquitetura formada por 3 gateways a localizac ¸ão dos veículos é estimada pela potência de sinal recebido, RSSI.…”
Section: Trabalhos Relacionadosunclassified
See 1 more Smart Citation
“…Therefore, due to these limitations, we found that these schemes are not suitable for a livestock tracking/monitoring application which is the focus of this work. Another proposal using LoRaWAN [153] comprises a combination of trilateration and the estimation of the LoRa channel for indoor localisation. Their approach requires that the device must be in the coverage of at-least three gateways but it also results in reasonably high error rates.…”
Section: Related Workmentioning
confidence: 99%